Genome-wide association study of brain amyloid deposition as measured by Pittsburgh Compound-B (PiB)-PET imaging - Yan, Qi; Nho, Kwangsik; Del-Aguila, Jorge L.; Wang, Xingbin; Risacher, Shannon L.; Fan, Kang-Hsien; Snitz, Beth E.; Aizenstein, Howard J.; Mathis, Chester A.; Lopez, Oscar L.; Demirci, F. Yesim; Feingold, Eleanor; et al. (Molecular psychiatry, 2021)
Deposition of amyloid plaques in the brain is one of the two main pathological hallmarks of Alzheimer’s disease (AD). Amyloid positron emission tomography (PET) is a neuroimaging tool that selectively detects in vivo amyloid deposition in the brain and is a reliable endophenotype for AD that complements cerebrospinal fluid biomarkers with regional information. We measured in vivo amyloid deposition in the brains of ~1000 subjects from three collaborative AD centers and ADNI using 11 C-labeled Pittsburgh Compound-B (PiB)-PET imaging followed by meta-analysis of genome-wide association studies, first to our knowledge for PiB-PET, to identify novel genetic loci for this endophenotype. The APOE region showed the most significant association where several SNPs surpassed the genome-wide significant threshold, with APOE*4 being most significant ( P -meta = 9.09E-30; β = 0.18). Interestingly, after conditioning on APOE*4 , 14 SNPs remained significant at P < 0.05 in the APOE region that were not in linkage disequilibrium with APOE*4 . Outside the APOE region, the meta-analysis revealed 15 non- APOE loci with P < 1E-05 on nine chromosomes, with two most significant SNPs on chromosomes 8 ( P- meta = 4.87E-07) and 3 ( P- meta = 9.69E-07). Functional analyses of these SNPs indicate their potential relevance with AD pathogenesis. Top 15 non- APOE SNPs along with APOE*4 explained 25–35% of the amyloid variance in different datasets, of which 14–17% was explained by APOE*4 alone. In conclusion, we have identified novel signals in APOE and non- APOE regions that affect amyloid deposition in the brain. Our data also highlights the presence of yet to be discovered variants that may be responsible for the unexplained genetic variance of amyloid deposition.